(untitled) (Scholars’ Journal, 2020)
Menstrual hygiene is the issue that is insufficiently acknowledged and given less attention from every sectors of development. Practice of proper hygiene during menstruation is very important as any small ignorance in hygiene during periods can increase the vulnerability to reproductive tract infection. This study was conducted in Sukhlaphanta-11, Kanchanpur district .The main objective of the study was to find out the understanding and practice of menstrual hygiene by girls and women. Descriptive research design under quantitative research method was adopted to conduct this study. Personal interview technique was used to collect data using pre-designed and structured questionnaire. Majority of the respondents were aware of menstruation before their menarche. Only 20.0% of the respondents always use sanitary pads as menstrual absorbent. Among the respondents using cloth as menstrual absorbent, 80.6% use the same cloth used during previous period. Majority (56.4%) of the respondents change their used menstrual material twice a day. Only 35.0% of the girls and women take bath daily during menstruation. Less than half of the respondents have knowledge on the washing of hands and genital part after every urination and pads change.